MODEL PEMBELAJARAN CHILDREEN LEARNING IN SCIENCE (CLIS) : EFEKTIVITASNYA TERHADAP HASIL BELAJAR MATEMATIKA PADA SISWA SEKOLAH DASAR - Kharisma Silvianingrum; Elly’s Mersina Mursidik; Rissa Prima Kurniawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students showed a lack of understanding of the material and lack of focus during learning, as seen from the results of observations. The teacher used the lecture method, so that students became passive and bored. This study aims to determine the effectiveness of the Childreen Learning In Science (CLIS) model on students' mathematics learning outcomes. This study uses a quantitative approach with a True Experimental Design type Posttest Only Control Group Design. The subjects of this study were students of SDN 01 Manisrejo with class IV A as the control class and class IV B as the experimental class. The sample in this study amounted to 44 students, namely students of SDN 01 Mansirejo consisting of class IV A as many as 22 students and class IV B as many as 22 students. The sampling technique in this study was Probability Sampling using the Simple Random Sampling type. The results showed that there was a significant difference in learning outcomes between students who used the Childreen Learning In Science (CLIS) learning model and using a learning model through the lecture method. Based on the results of the Posttest, the average experimental class was 90.90 and the control class was 63.40. Hypothesis testing was carried out using the T-test with a significant level of 0.000 < 0.05, so the Children's Learning In Science (CLIS) model is effective for students' mathematics learning outcomes.